Multi-Trait Analysis of GWAS and Biological Insights Into Cognition: A Response to Hill (2018). (13th July 2018) - Lam, Max; Trampush, Joey W.; Yu, Jin; Knowles, Emma; Djurovic, Srdjan; Melle, Ingrid; Sundet, Kjetil; Christoforou, Andrea; Reinvang, Ivar; DeRosse, Pamela; Lundervold, Astri J.; Steen, Vidar M.; et al.
Abstract : Hill (Twin Research and Human Genetics, Vol. 21, 2018, 84–88) presented a critique of our recently published paper in Cell Reports entitled 'Large-Scale Cognitive GWAS Meta-Analysis Reveals Tissue-Specific Neural Expression and Potential Nootropic Drug Targets' (Lam et al., Cell Reports, Vol. 21, 2017, 2597–2613 ). Specifically, Hill offered several interrelated comments suggesting potential problems with our use of a new analytic method called Multi-Trait Analysis of GWAS (MTAG) (Turley et al., Nature Genetics, Vol. 50, 2018, 229–237). In this brief article, we respond to each of these concerns. Using empirical data, we conclude that our MTAG results do not suffer from 'inflation in the FDR [false discovery rate]', as suggested by Hill ( Twin Research and Human Genetics, Vol. 21, 2018, 84–88), and are not 'more relevant to the genetic contributions to education than they are to the genetic contributions to intelligence'.